Efek Penambahan Penguat Serat Bambu Andong dan Serat Kaca pada Komposit untuk Aplikasi Badan Speed Boat - Daffa Alvian Iswandi; Andi Lamappasessu; Dwi Rahmalina (Fakultas Teknik Universitas Pancasila, 2023)
In materials technology, natural fibers can be employed as reinforcing materials to create materials that are lightweight, strong, environmentally friendly, and inexpensive. Bamboo is sturdy, light in weight, and simple to work with. The hull of a ship is the most critical component, and it needs to be made of material that is both strong and light. The hand-lay-up method is employed throughout the composite sheet invoice process. Reinforcing fiber content in composite material sheets varies by 4%, 5%, and 6% between the two types of fibers used: glass fiber and bamboo fiber. ISO 14125 Bending Test and ISO 527-4 Tensile Test According to the results of tensile testing on andong bamboo fiber, code A, which consists of 4% fiber and 96% matrix, has a significant strength value, and code C, which consists of 6% glass fiber and 94% matrix, has a significant strength value. According to the results of the bending test for bamboo fiber, code A, which consists of 4% fiber and 96% matrix, has a significant strength value. According to the results of research on the type of glass fiber, code C, which consists of 6% glass fiber and 94% matrix, has a significant strength value.